PENGARUH BUDAYA ORGANISASI, GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN - Novita Sari; Dian Septianti (JURNAL KOMPETITIF, 2020)
Performance is the result of work achieved by an employee in carrying out tasks in accordance with their responsibilities. There are many factors that affect performance, but in this study only a few factors will be discussed including organizational culture, leadership style and physical work environment. Organizational culture is a pattern of beliefs and organizational values that are understood, imbued and practiced by the organization and become the basis for rules of behavior in the organization so as to encourage motivation and improve performance. While the leadership style is one of the main factors that support the success of the organization in achieving goals and improving performance. Other factors, namely the physical work environment is considered important because it has a direct influence on employees in carrying out the work. The design used in this research is descriptive qualitative research. Keywords: Organizational Culture, Leadership Style, Physical Work Environment, Employee Performance